Out of scope? - Indefinite nominal subjects and objects preceding the negative marker in Middle Welsh - Sackmann, Raphael (Studia Celtica Posnaniensia, 2024)
While the diachronic development of negation in Welsh has been subject to extensive research (see Willis 2006, 2013, in particular), Middle Welsh negative (matrix) clauses are under-researched in a synchronic perspective (Poppe in press). There is no consensus on syntactic analyses of verb-second negative matrix clauses, especially those with subject-verb and object-verb order. In (Modern) Irish, native speakers generally interpret comparable “Narrative Fronting” constructions with scope of negation over a fronted indefinite. However, in Middle Welsh, instances of wide-scope indefinites can be found, while scope relations are potentially ambiguous in others. For object-verb clauses, matters are further complicated by the occasional presence of an additional object clitic. This chapter draws attention to such arguably challenging Middle Welsh examples and discusses possible interpretations of indefinites with respect to the notion of topicality, as well as complexities of their related syntactic analyses. With an attempt to relativize apparently conflicting views in previous research, potential syntactic structures are specified, primarily with respect to non-topical indefinites that, at least on the surface, appear to be out of scope. For these (and other phrases occurring in this construction, occasionally also definites), a syntactic derivation is formulated, which can arguably be compared with certain Focus Fronting constructions in other languages.